Pengaruh Ujaran Kebencian Admin @KeretaCepatID pada sosok Patrick Kluivert (Pelatih Timnas) terhadap Tingkat Persepsi Followers di Media Sosial X - Brigita Probowati; A Yuda Triartanto; Akhmad Syafrudin Syahri (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Social media has become a new communication space that allows for the rapid and widespread dissemination of information, including on public issues. One of the platforms that is often used is social media X (formerly Twitter), where users can express their opinions and shape public perception. This study is entitled